Pembelajaran Berbasis Proyek melalui Pembuatan Alat Peraga Sistem Pernapasan untuk Meningkatkan Antusiasme Belajar Siswa SD - Siti Inganah; Magfirah Magfirah (Universitas Sebelas Maret, 2025)
This article is a best practice in implementing project-based learning (PjBL), on the human respiratory system material in the fifth grade at SD Inpres Pannujuang. This activity was carried out through a project to create a respiratory system teaching aid using simple materials. This practice aims to increase students' enthusiasm for learning through their involvement in the direct learning process. Students showed increased interest, active engagement, and high curiosity towards the material during the implementation. They collaborated in groups, communicated, and were very creative in making teaching aids. This activity shows that project-based learning not only enhances students' understanding of concepts but also boosts their enthusiasm for learning. This method can be used as an alternative for enjoyable, meaningful, and contextual IPAS learning.